2020
DOI: 10.1007/s13238-020-00773-z
|View full text |Cite
|
Sign up to set email alerts
|

Graded and pan-neural disease phenotypes of Rett Syndrome linked with dosage of functional MeCP2

Abstract: Rett syndrome (RTT) is a progressive neurodevelopmental disorder, mainly caused by mutations in MeCP2 and currently with no cure. We report here that neurons from R106W MeCP2 RTT human iPSCs as well as human embryonic stem cells after MeCP2 knockdown exhibit consistent and long-lasting impairment in maturation as indicated by impaired action potentials and passive membrane properties as well as reduced soma size and spine density. Moreover, RTT-inherent defects in neuronal maturation could be pan-neuronal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…From this result we conclude that RTT neurons have increased excitability. A recent study on R106W missense iPSC derived neurons also found a graded response in some morphological features and electrophysiological properties compared to MECP2 knockdown neurons, and also did not detect changes in synaptic function that were evident in knockdown neurons (44). In our case we also examined Na + and K + currents in CLT L124W and MECP2 null neurons, and found these currents are consistently decreased relative to those in WT.…”
Section: L124w Cellular and Network Core Phenotypessupporting
confidence: 47%
“…From this result we conclude that RTT neurons have increased excitability. A recent study on R106W missense iPSC derived neurons also found a graded response in some morphological features and electrophysiological properties compared to MECP2 knockdown neurons, and also did not detect changes in synaptic function that were evident in knockdown neurons (44). In our case we also examined Na + and K + currents in CLT L124W and MECP2 null neurons, and found these currents are consistently decreased relative to those in WT.…”
Section: L124w Cellular and Network Core Phenotypessupporting
confidence: 47%
“…From this result we conclude that RTT neurons have increased excitability because they have a greater chance to trigger an action potential with a given depolarizing current. A recent study on R106W missense iPSC derived neurons also found a graded response in some morphological features and electrophysiological properties compared to MECP2 knockdown neurons, and did not detect changes in synaptic function that were evident in knockdown neurons [ 46 ]. In our case we also examined Na + and K + currents in CLT L124W and MECP2 null neurons, and found these currents are consistently decreased relative to those in WT.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the nuclear size correlates with transcriptional activity [36], it is meaningful that our mildest variant impacts scarcely or later on the MECP2 transcriptional activity. Some studies discriminate between nuclear size and soma size [34], but according to our analyses the two parameters overlap. Chen at al [34] noticed a similar nuclear size in iPSC neurons expressing the p.Arg106Trp and isogenic WT lines, while it was consistently reduced in the neurons derived from knockout iPSCs.…”
Section: Discussionmentioning
confidence: 79%
“…At the same precocious neuronal differentiation stage, we analyzed dendritic complexity and neuronal length, which have been reported as defective in mature neurons [32][33][34]. An overview of the morphological appearance of CTRL, PtY, PtA1, PtA2, and PtB1 neurons is provided in Figure 5a, while panels b, c, and d summarize the results of the statistical analyses.…”
Section: Morphological Analyses Of Rtt Young Neuronsmentioning
confidence: 99%